The use of ChatGPT in Teacher Training to Improve Pedagogical Competencies - Rao, Ananya; Gupta, Meera; Joshi, Nikhil (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
The integration of Artificial Intelligence (AI) tools like ChatGPT in education has the potential to transform teacher training by enhancing pedagogical competencies. Teacher training programs face challenges in preparing educators with the necessary skills to engage students, design effective lessons, and adapt to diverse learning environments. AI tools, particularly language models like ChatGPT, offer opportunities to simulate real-world teaching scenarios, provide personalized feedback, and support teachers in their professional development. This study aims to explore the use of ChatGPT in teacher training programs to improve pedagogical competencies, focusing on areas such as lesson planning, student engagement, and instructional strategies. A mixed-methods approach was used, combining quantitative assessments of pedagogical competencies with qualitative feedback from teacher trainees. The study involved 150 teacher trainees who utilized ChatGPT for interactive simulations, lesson design assistance, and reflective practice over a 10-week period. The results indicate that the use of ChatGPT significantly improved the trainees’ lesson planning skills, ability to engage students, and adapt teaching strategies to diverse learners. Trainees also reported increased confidence in applying pedagogical knowledge in real classroom settings. This study concludes that ChatGPT can be an effective tool in teacher training, helping to enhance pedagogical competencies and provide personalized support for educators’ professional growth.